Przyczyna dalsza wykluczenia nierozerwalności małżeństwa w świetle współczesnego orzecznictwa Roty Rzymskiej (2000-2012) - Góralski, Wojciech (Ius Matrimoniale, 2020)
Indissolubility is an essential attribute of marriage derived from God's law, and the exclusion of indissolubility renders the marriage null and void (can. 1101 § 2 CIC). In proving exclusio boni sacramenti, an extremely important role is played by the indication of the cause (motive) of the simulation act, including the further cause (causa remota). Although this reason is not directly related to a particular marriage, it – to some extent – influences the will of the spouse rejecting the attribute of indissolubility. When it comes to the reasons for the further exclusion of the indissolubility of marriage, three basic ones can be discerned in the most recent rotal jurisprudence: a mentality favoring the institution of divorce, the lack of sufficient religious formation and the special personality of contractors. The postulate of priests, during the canonical pre-wedding examination, to pay close attention to the convictions and views of the spouses regarding the indissolubility of marriage seems fully justified.